Assessment of burnout, resilience, and thriving among academic health professionals: findings from an international study - Nahas, Abdul Rahman Fata; Elnaem, Mohamed Hassan; Mubarak, Naeem; Khatwa, Merna Abou; Barakat, Muna; Faller, Erwin; Kassem, Lamyaa M.; Ramatillah, Diana Laila; Jaber, Ammar; Akkawi, Muhammad Eid; Al-Shami, Abdulkareem Mohammed; Chandran, Sarath; et al. (Frontiers in Public Health, 2024)
Introduction: Burnout, resilience, and thriving significantly impact academics, particularly in health professions, where responsibilities are extensive. This study aimed to explore these constructs among health sciences academics, examining sociodemographic and work-related factors influencing these outcomes.A cross-sectional study was conducted among health professions academics via web-based professional networks from August 2022 to February 2023. Validated tools were used, and descriptive and inferential statistics were applied.Results: 505 participants were included, predominantly female (63%), with a mean age of 38.15 ± 9.6 years. High burnout was reported by 10.9%, 13.7% experienced exhaustion, and 6.3% were disengaged. Resilience and thriving were moderate at 59.2% and 51.9%, respectively. Age correlated negatively with burnout (r = -0.131, p = 0.003) but positively with resilience (r = 0.178, p < 0.001).Females reported higher exhaustion (p = 0.014), while males showed greater resilience (p = 0.016).Instructors exhibited lower resilience compared to assistant professors (p<0.001) and associate professors (p<0.001). Those at public universities reported higher exhaustion than those at private universities (p < 0.001).Variable levels of burnout, resilience, and thriving were observed among health sciences academics, influenced by sociodemographic and work-related factors. Interventions targeting resilience and thriving may mitigate burnout risk and enhance engagement among academics in health professions.